2020
DOI: 10.1155/2020/8615410
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy of Catheter Ablation and Left Atrial Appendage Closure for Patients with Atrial Fibrillation: A Case-Control Study

Abstract: Aim. The feasibility and safety of performing the combined procedure of catheter ablation (CA) and left atrial appendage closure (LAAC) for atrial fibrillation (AF) have been reported by observational studies without controls. The aim of this study was to compare the procedural and long-term outcomes of combined procedures with isolated CA or LAAC. Methods and Results. This study included patients who underwent combined CA and LAAC (combined group), CA alone (CA-only group), or LAAC alone (LAAC-only group). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Our results showed that the AF recurrence rate of the combined group was comparable with that of the CA-only group during 1 years follow-up, indicating that additional LAAC did not influence the recurrence rate of atrial fibrillation. This finding is in line with previous literature (24,25). Moreover, Persistent AF, even long-standing persistent AF, is difficult to treat inasmuch as arrhythmia recurs at significant rates after catheter ablation therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the AF recurrence rate of the combined group was comparable with that of the CA-only group during 1 years follow-up, indicating that additional LAAC did not influence the recurrence rate of atrial fibrillation. This finding is in line with previous literature (24,25). Moreover, Persistent AF, even long-standing persistent AF, is difficult to treat inasmuch as arrhythmia recurs at significant rates after catheter ablation therapy.…”
Section: Discussionsupporting
confidence: 92%
“…After a mean follow-up of 726 ± 91 days, the annualized stroke and major bleeding rates were 1.09% and 1.09%, respectively. We recently reported the results of the combined procedure in a case-control study using the propensity score matching method [ 7 ]. Outcomes of the combined procedure with ablation alone and LAAC alone were compared.…”
Section: Discussionmentioning
confidence: 99%
“…The combined procedure was performed as described previously [ 7 ]. AF ablation was performed before LAAC implantation.…”
Section: Methodsmentioning
confidence: 99%
“…The flowchart of the study selection process was shown in Figure 1. In total, 16 studies were included, 13,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and one of the studies was divided into two arms for meta-analysis according to the procedural strategies (First LAAC then RFA or First FRA then LAAC), 35…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…12 Preliminary studies showed that the procedure of combined ablation and LAAC could be performed successfully and safely, with a more than 95% success rate and a less than 5% periprocedural adverse event. 13,14 Additionally, meta-analyses revealed the short-term efficacy and safety of the combined procedure for AF patients with high stroke risk. 15,16 Despite the promising results, the limitation of previous studies should be highlighted, including a small sample size (e.g., less than ten patients), [17][18][19] lack of long-term follow-up (e.g., less than 6 months), [20][21][22] and noncombined ablation and LAAC.…”
Section: Introductionmentioning
confidence: 99%